A BIBLIOMETRIC AND VISUAL ANALYSIS OF RESEARCH ON DUAL-QUALIFIED TEACHERS IN CHINESE HIGHER VOCATIONAL EDUCATION USING CITESPACE (2015–2025) - Wang , Yuanyuan; Yun , Fah Chang; Kamaruddin , Halim Shukri (INTERNATIONAL JOURNAL OF LAW, GOVERNMENT AND COMMUNICATION (IJLGC), 2025)
This study conducts a bibliometric and visual analysis of research on dual-qualified teachers in Chinese higher vocational education from 2015 to 2025, aiming to uncover theoretical foundations, development trends, and competency-performance linkages. In the field of medical and health-related vocational education, the demand for dual-qualified teachers—those who combine theoretical knowledge with practical industry experience—is especially pressing. However, existing research remains fragmented, lacks performance-based evaluation frameworks, and does not fully address the specific demands of the healthcare sector. Given the localized institutional background of dual-qualified teachers in China, this study analyses literature published between 2015 and 2025 using the CNKI database. CiteSpace 6.3.R1 was employed to visualize knowledge structures through keyword co-occurrence, author collaboration networks, institutional mapping, and thematic evolution. Classical competency frameworks such as the Iceberg Model and the Onion Model are integrated with performance theories including Expectancy Theory, Social Comparison Theory, and Goal-Setting Theory to develop an analytical framework tailored to the specific demands of the research context. The findings reveal five core competency dimensions: t knowledge, skills, professional ethics, personal traits, and motivation. These are aligned with two performance dimensions—outcome-based (teaching quality, research, enterprise practice) and conduct-based (professional ethics). Three key trends are identified: (1) growing alignment between competency standards and performance metrics since 2020, driven by national policy reforms; (2) fragmented author networks reflecting limited academic consolidation; and (3) concentration of research within provincial-level institutions, with limited cross-regional collaboration. By combining bibliometric analysis with theoretical synthesis, this study not only highlights the intellectual trajectory of dual-qualified teacher research in China but also proposes a comprehensive, performance-linked competency framework. The results offer theoretical foundations and practical implications for competency assessment, policy development, and teacher training in the context of medical vocational education.